A method for manufacturing anti-static floor using magnetic carbon fiber
By using magnetic carbon fibers in the anti-static floor and applying a magnetic field, they are arranged vertically during the construction process, and the problems of high carbon fiber addition, high cost and low efficiency in the construction of conductive networks in the prior art are solved, thereby achieving efficient and low-cost conductive network construction and excellent anti-static performance.
Patent Information
- Application Number
- CN202411988228.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
AI Technical Summary
When using carbon fiber in existing anti-static floors, a higher proportion of carbon fiber is needed to build a conductive network, resulting in increased material costs, affected mechanical properties and poor floor color. It is difficult for traditional construction methods to achieve upright arrangement of carbon fibers, resulting in low efficiency in forming conductive paths.
Magnetic carbon fibers are used and driven by magnetic fields to enable vertical arrangement of carbon fibers during construction, so as to quickly build a conductive network with low addition amount. The development and application of magnetic carbon fibers can not only reduce the amount of conductive materials, but also reduce the impact on floor color, while improving construction efficiency and anti-static performance.
Through the use of magnetic carbon fiber, it is possible to quickly build an efficient conductive network with low addition amount, reduce material costs, improve the mechanical properties and appearance of the floor, and improve anti-static performance and construction efficiency.
Smart Images

Figure CN119737032A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flooring, and in particular to a method for manufacturing an antistatic flooring by utilizing magnetic carbon fibers. Background Art
[0002] As a special functional material, anti-static flooring is widely used in electronic factories, laboratories, pharmaceutical workshops and other places with high requirements for electrostatic protection. This type of flooring achieves the anti-static function by constructing a conductive network system to achieve effective charge conduction. The selection of conductive materials and construction technology play a vital role in the performance of the floor. In the prior art, commonly used conductive materials include carbon fiber, carbon nanotubes and conductive fillers. Among them, carbon fiber has become an important material in anti-static flooring due to its excellent conductivity, mechanical properties and chemical corrosion resistance.
[0003] However, the use of carbon fiber also faces some challenges, such as high addition amount. In order to build an effective conductive network in the floor, a higher proportion of carbon fiber needs to be added. This not only increases the material cost, but may also affect the mechanical properties and construction process of the floor. Carbon fiber, as a carbon-based material, has a dark color characteristic. When it is used in large amounts, it will significantly affect the color of the floor, making it difficult for the appearance of the floor to meet the aesthetic requirements of certain places. There is also the difficulty of constructing a conductive network. In traditional construction methods, the distribution of carbon fiber in the coating is usually random, and it is impossible to achieve upright arrangement. The efficiency of forming a conductive path is low, resulting in the need to increase the amount of carbon fiber to meet the conductivity requirements. In order to solve the above problems, a method for manufacturing an anti-static floor using magnetic carbon fiber is proposed. Summary of the invention
[0004] The purpose of the present invention is to provide a technology that utilizes magnetic carbon fibers, which can be driven by a magnetic field to achieve vertical arrangement of the carbon fibers during floor construction, thereby quickly building a conductive network at a low addition amount. The development and application of magnetic carbon fibers can not only reduce the amount of conductive materials used, but also significantly reduce the impact on the color of the floor, while improving construction efficiency and anti-static performance.
[0005] To achieve the above object, the present invention proposes the following technical solution: a method for manufacturing an anti-static floor using magnetic carbon fiber, comprising the following steps:
[0006] Step 1, synthesizing magnetic carbon fiber. The method for synthesizing magnetic carbon fiber includes a pre-synthesis method and a post-synthesis method. The steps of the pre-synthesis method are as follows: the pre-oxidized fiber precursor is immersed in a mixed solution of ferrous chloride and ferric chloride, the concentration ratio of ferrous chloride and ferric chloride is 1 mol: 1 mol, and the pH is adjusted with a sodium hydroxide solution to precipitate ferrous ions and ferric ions, which are evenly loaded on the pre-oxidized fiber precursor. After pre-oxidation and carbonization, the carbon fiber can be magnetic when it is generated, and then the obtained fiber is chopped;
[0007] The steps of the post-synthesis method are as follows: the formed carbon fiber is chopped and soaked in a ferrous ion solution, and then an alkaline substance is added to precipitate the ferrous iron, generating ferrous oxide that precipitates on the carbon fiber. The water temperature is raised to 70-80°C, and the ferrous oxide on the carbon fiber will slowly oxidize into ferroferric oxide, making the carbon fiber magnetic;
[0008] Step 2: Mixing: After the prepared carbon fiber is made into a predetermined length, it is evenly mixed into the floor coating at a weight ratio of 0.1%, and construction is carried out on the conductive layer. During the construction, a vertical magnetic field of a preset strength is applied to make the carbon fiber stand upright under the action of the magnetic field.
[0009] Further, in the present invention, the steps of the pre-synthesis method in step 1 are as follows:
[0010] Pretreatment: Select high-quality pre-oxidation fiber precursor, the pre-oxidation fiber precursor is PAN fiber, wash it with deionized water to remove surface impurities and oil stains;
[0011] Soaking reaction: The cleaned PAN fiber is immersed in a solution of ferrous chloride and ferric chloride, and the concentration of iron salt in the solution is configured at 1 mol:1 mol, so that the iron ions in the solution can completely penetrate into the fiber surface;
[0012] Precipitation formation: add an appropriate amount of sodium hydroxide solution and adjust the solution pH to 8-10, so that ferrous ions and ferric ions undergo precipitation reaction and are evenly loaded on the surface of the fiber before oxidation to form a magnetic metallization layer;
[0013] Pre-oxidation and carbonization: The fiber loaded with iron salt is heated to 250-300℃, and pre-oxidation reaction is carried out in air to form a stable iron oxide phase, and then carbonization treatment is carried out, and heating to 1000-1500℃ in a nitrogen atmosphere to generate carbon fiber and realize magnetism at the same time;
[0014] Cutting and finishing: The prepared magnetic carbon fiber is chopped into short pieces to obtain fiber segments of a certain length for subsequent use.
[0015] Further, in the present invention, the steps of the post-synthesis method in step 1 are as follows:
[0016] Carbon fiber preparation: select short chopped segments of waste carbon fiber through the waste carbon fiber recycling process, wash and dehydrate with deionized water to ensure that there are no impurities on the carbon fiber surface;
[0017] Soaking in ferrous solution: Soak the cleaned carbon fiber in a ferrous ion solution of a certain concentration to ensure that the carbon fiber fully absorbs the ferrous ions;
[0018] Precipitation reaction: slowly add sodium hydroxide solution to adjust the solution pH to 8-10 to promote the precipitation reaction of ferrous ions to generate ferrous oxide;
[0019] Heating oxidation: Immerse the soaked carbon fiber in a heating tank, raise the water temperature to 70-80°C, and maintain it for several hours to slowly oxidize the ferrous oxide on the surface of the carbon fiber into ferroferric oxide;
[0020] Magnetic activation uses high-frequency electromagnetic fields or electrostatic fields to activate the magnetic material on the surface of carbon fiber, so that it forms magnetism with controllable directionality and strength;
[0021] Surface treatment: Plasma treatment or amino treatment is performed to enhance the adhesion of carbon fiber to the coating.
[0022] Further, in the present invention, the details of step 2 are as follows:
[0023] Step 2.1, carbon fiber processing and mixing, first adjust the length of the magnetic carbon fiber according to the needs of the floor coating to match the floor thickness, and adjust the fiber length by mechanical cutting or chemical methods to obtain the best conductivity and coating uniformity;
[0024] The surface treatment technology is used to make the surface have good hydrophilicity or lipophilicity to enhance the bonding force with the coating. The surface treatment technology includes amino treatment, acid washing or plasma treatment;
[0025] Guided by magnetic field, the prepared carbon fiber and coating are mixed at a weight ratio of 0.1% and evenly distributed. During the coating application process, a strong vertical magnetic field is applied so that the magnetic carbon fiber is arranged into an upright shape under the action of the magnetic field, thereby optimizing the conductive network structure of the fiber;
[0026] Step 2.2, coating construction, floor coating, apply the evenly mixed magnetic carbon fiber coating to the floor surface, apply a vertical magnetic field of a certain strength during the construction process, and adjust the strength and direction of the magnetic field as needed to ensure that the carbon fibers are arranged in an upright manner during construction;
[0027] Heat treatment: After the coating is applied, it is dried and cured in a temperature-controlled environment, heated to 60-80°C to ensure that the coating is cured and the carbon fiber can maintain its upright state;
[0028] Testing and optimization: Conduct resistance testing on the finished floor coating to ensure that the density of the carbon fiber meets the anti-static requirements within a 77mm diameter circle area by adjusting the amount of carbon fiber in the coating and the strength of the magnetic field;
[0029] Step 2.3, post-construction treatment, gloss adjustment, apply special gloss adjuster or transparent protective film on the coating, anti-wear treatment, add wear-resistant additives to the coating, wear-resistant additives include nano silicon, polyurethane materials to improve the hardness and scratch resistance of the coating.
[0030] Furthermore, in the present invention, the step 2.1 uses a dynamic frequency conversion magnetic field technology, and the frequency range f field =50-200Hz, dynamically change the magnetic field frequency to prevent carbon fibers from gathering in the coating, calculation formula:
[0031]
[0032] D fiber : Carbon fiber distribution uniformity index;
[0033] ρ fiber : The bulk density of carbon fiber, in g / cm 3 ;
[0034] B field : applied magnetic field strength, unit: mT;
[0035] L fiber : The length of carbon fiber, in mm.
[0036] Furthermore, in the present invention, the magnetic field is kept stable during the curing process of step 2.2 to ensure that the carbon fibers remain vertically aligned after the coating is cured. The calculation formula is:
[0037] S align : Fiber alignment coefficient, the value is between 0 and 1, 1 means completely vertical;
[0038] θ i : The angle between the ith fiber and the vertical direction;
[0039] n: The number of fibers tested. The above formula is used to monitor the effect of the magnetic field and ensure the efficient construction of the conductive network of carbon fibers inside the coating.
[0040] Furthermore, in the present invention, step 2.3 also includes coating performance optimization and post-processing, and the resistance performance is optimized by adjusting the mass ratio of carbon fibers or the magnetic field strength, and the calculation formula is:
[0041]
[0042] Rarea : Surface resistance of coating, unit Ω;
[0043] ρ fiber : Resistivity of carbon fiber, unit: Ω·cm;
[0044] H floor : coating thickness, unit: cm;
[0045] A contac : Test electrode contact area, unit: cm 2 , which is used to guide the optimization of the conductive properties of the coating by adjusting parameters, including fiber density and length, to achieve the target resistance value and ensure antistatic performance.
[0046] Furthermore, in the present invention, the specific steps of the process flow of recycling waste carbon fiber in the post-synthesis method of step 1 are as follows:
[0047] Step 1: Pretreatment of waste carbon fiber: first, classify the waste carbon fiber, soak the waste carbon fiber in deionized water, clean the surface dirt, grease, and resin pollutants, use acid or alkali washing to remove surface impurities according to the degree of pollution, and enhance the cleaning effect by ultrasonic cleaning, hot water cleaning or mechanical brushing. The cleaned carbon fiber is dehydrated with drying equipment;
[0048] Step 2: Recover and remove the resin by pyrolysis or chemical dissolution;
[0049] Step 3: Soak the waste carbon fiber cleaned in step 2 in an oxidant solution to oxidize the surface of the carbon fiber to form oxygen-containing functional groups. The oxidation time and efficiency formula is:
[0050] Among them, E oxidation is the surface oxidation efficiency, A after is the surface energy of the carbon fiber surface after oxidation treatment, in mJ / m 2 , A before is the surface energy of the carbon fiber surface before oxidation treatment, in mJ / m 2 ;
[0051] Step 4: Magnetic enhancement treatment, magnetic material is soaked or chemically deposited onto the surface of waste carbon fiber, magnetic loading efficiency formula:
[0052] Among them, E mag is the magnetic material loading efficiency, M mag_loaded is the mass of the magnetic material loaded, in g, M total_fiber is the mass of waste carbon fiber, in g.
[0053] Furthermore, in the present invention, the pyrolysis method heats the waste carbon fiber to 200-800°C, performs pyrolysis treatment in an inert gas atmosphere, removes the resin, and removes different types of resin by controlling the temperature gradient. The pyrolysis temperature formula is:
[0054] T opt : The optimal temperature for pyrolysis, T0: Initial starting temperature, indicating the minimum starting temperature for the pyrolysis reaction of the resin, M resin n: The mass of the resin, in g, affects the pyrolysis temperature requirement, C resin : The specific heat capacity of the resin, in J / g·K, indicates the heat characteristics required for the pyrolysis of the resin. The specific heat capacity of polyester resin is 1.25 J / g·K, and the specific heat capacity of epoxy resin is 1.45 J / g·K. The rate of change of resin mass with time during pyrolysis (g / min), indicating the rate of resin decomposition, k1, k2, k3: empirical coefficients, used to correct the influence of each parameter, determined according to experimental data: k1: coefficient of pyrolysis temperature with increase of resin mass, with a value of 0.4-0.6; k2: coefficient of pyrolysis temperature with change of resin specific heat capacity, with a value of 10-20, k3: coefficient of pyrolysis temperature with change of resin decomposition rate, with a value of 5-10;
[0055] In order to optimize the smoothness of temperature change, the formula for controlling the temperature gradient is:
[0056] Temperature gradient over time ℃ / min. T opt : Target pyrolysis temperature ℃, T current : Current temperature ℃, t ramp : The time required for heating up min, by adjusting t ramp , control the heating rate to make the resin decomposition more stable and avoid thermal damage to the carbon fiber surface caused by excessive heating;
[0057] Inert gas improves efficiency during pyrolysis by removing volatiles. The gas flow rate v gas The optimization formula is:
[0058] v gas : gas flow rate L / min, k4: gas flow rate influence coefficient, the value is 0.1-0.2, M resin : Initial mass of resin g. A fiber : Surface area of carbon fiber m 2 , calculated by fiber diameter and length, t gas : Gas residence time in the pyrolysis device min.
[0059] Beneficial effects: The technical solution of this application has the following technical effects:
[0060] 1. The pre-synthesis method of the present invention loads metal iron salts in the fiber precursor before oxidation, and the formed iron oxide and carbon fiber are well combined, so that the magnetic carbon fiber finally obtained has stable magnetism. The post-synthesis method utilizes waste carbon fiber and enhances the magnetism through secondary treatment, which promotes resource recovery and reuse. Iron salt deposition and oxidation reaction: In the pre-synthesis method, iron salts are evenly loaded on the surface of the fiber before oxidation through precipitation reaction. After pre-oxidation and carbonization, the combination of the generated magnetic metal oxide and carbon fiber has strong chemical stability, thereby ensuring the long-term magnetic performance of carbon fiber in floor coatings. The process of converting ferrous oxide into ferroferric oxide in the post-synthesis method further enhances the magnetism of carbon fiber through heating and magnetic field activation, ensuring the uniformity and magnetic stability of magnetic carbon fiber.
[0061] 2. Fiber alignment mechanism guided by magnetic field The fibers are arranged in a directional manner in the magnetic field. During the construction process, by applying a vertical magnetic field, the magnetic carbon fibers form an upright arrangement under the action of the external magnetic field. This arrangement optimizes the conductivity and distribution uniformity of the carbon fibers. Magnetic field guidance can effectively prevent the aggregation or sedimentation of carbon fibers in the coating, enhance the conductive network structure of the coating, and make the floor coating have higher antistatic properties and long-term stability.
[0062] The dynamically changing magnetic field frequency (50-200Hz) can prevent carbon fibers from agglomerating in the coating, thereby improving the uniformity of carbon fiber distribution (controlled by the Dfiber index) and further optimizing the conductivity of the floor coating. By dynamically adjusting the magnetic field frequency, the distribution of fibers in the coating can be precisely controlled to achieve optimal conductivity.
[0063] 3. Surface hydrophilicity or lipophilicity treatment: In step 2.1, the surface modification techniques such as amino treatment, acid washing or plasma treatment can make the surface of magnetic carbon fiber have better hydrophilicity or lipophilicity. This surface modification increases the adhesion between carbon fiber and floor coating, ensures the stable distribution of carbon fiber in the coating, and further improves the wear resistance and long-term antistatic effect of the coating.
[0064] 4. The anti-static effect of floor coating is better, and the resistance performance is optimized. The addition of magnetic carbon fiber makes the floor coating have good conductivity. By calculating and adjusting the mass ratio, length and magnetic field strength of the carbon fiber, the resistance (Rarea) of the coating can be accurately controlled. The optimization of this process ensures that the floor coating meets the anti-static requirements and reduces static electricity accumulation. It is especially suitable for strict anti-static environments such as electronic factories and laboratories. The coating resistance is optimized. By adjusting the amount of carbon fiber and the applied magnetic field strength, the floor coating can reach a specific resistance value, thereby ensuring that the coating will not lose its anti-static function during long-term use. This method can also accurately achieve the target resistance through detection and real-time adjustment during the construction process, ensuring the efficiency and stability of the anti-static floor coating.
[0065] 5. The post-synthesis method in this method recycles waste carbon fiber and removes its surface resin by pyrolysis or chemical dissolution, which not only realizes the reuse of carbon fiber, but also reduces the cost of raw materials in the production process. In addition, after oxidation and magnetic enhancement treatment, waste carbon fiber has strong magnetism and good performance, so that the waste is maximized and meets the needs of sustainable development.
[0066] In short, the present invention has excellent overall performance and an efficient conductive network structure. By accurately controlling the length, distribution, surface treatment and other factors of the carbon fiber, an efficient conductive network structure is formed in the coating, making the antistatic effect of the floor more durable and stable. Through the calculation formula, various parameters are adjusted to achieve the target resistance value, thereby ensuring the conductivity and antistatic effect of the coating. The method optimizes the preparation process of magnetic carbon fiber and the performance of floor coating from many aspects. By controlling the magnetism, arrangement and distribution uniformity of carbon fiber, and combining the recycling of waste carbon fiber, not only the antistatic function of the coating is improved, but also the recycling of resources and environmental protection are realized, which has significant technical advantages and market application prospects.
[0067] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered to be part of the inventive subject matter of the present disclosure, provided such concepts are not mutually inconsistent.
[0068] The foregoing and other aspects, embodiments and features of the present invention can be more fully understood from the following description in conjunction with the accompanying drawings. Other additional aspects of the present invention, such as the features and / or beneficial effects of the exemplary embodiments, will be apparent from the following description or learned from the practice of the specific embodiments according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] The drawings are not intended to be drawn to scale. In the drawings, each identical or nearly identical component shown in various figures may be represented by the same reference numeral. For clarity, not every component is labeled in every figure. Embodiments of various aspects of the present invention will now be described by way of example and with reference to the accompanying drawings, in which:
[0070] Figure 1 It is a schematic diagram of the magnetic carbon fiber antistatic floor of the present invention.
[0071] Figure 2 This is a top view of the magnetic carbon fiber antistatic floor of the present invention.
[0072] Figure 3 This is a schematic diagram of a conventional carbon fiber antistatic floor.
[0073] Figure 4 This is a top view of a conventional carbon fiber antistatic floor. DETAILED DESCRIPTION
[0074] In order to better understand the technical content of the present invention, specific embodiments are cited and described as follows in conjunction with the accompanying drawings. Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily defined to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways, because the concepts and embodiments disclosed in the present invention are not limited to any implementation. In addition, some aspects disclosed in the present invention can be used alone, or in any appropriate combination with other aspects disclosed in the present invention.
[0075] A method for manufacturing an anti-static floor using magnetic carbon fiber comprises the following steps:
[0076] Step 1, synthesizing magnetic carbon fiber. The method for synthesizing magnetic carbon fiber includes a pre-synthesis method and a post-synthesis method. The steps of the pre-synthesis method are as follows: the pre-oxidized fiber precursor is immersed in a mixed solution of ferrous chloride and ferric chloride, the concentration ratio of ferrous chloride and ferric chloride is 1 mol: 1 mol, and the pH is adjusted with a sodium hydroxide solution to precipitate ferrous ions and ferric ions, which are evenly loaded on the pre-oxidized fiber precursor. After pre-oxidation and carbonization, the carbon fiber can be magnetic when it is generated, and then the obtained fiber is chopped;
[0077] The steps of the post-synthesis method are as follows: the formed carbon fiber is chopped and soaked in a ferrous ion solution, and then an alkaline substance is added to precipitate the ferrous iron, generating ferrous oxide that precipitates on the carbon fiber. The water temperature is raised to 70-80°C, and the ferrous oxide on the carbon fiber will slowly oxidize into ferroferric oxide, making the carbon fiber magnetic;
[0078] Step 2: Mixing: After the prepared carbon fiber is made into a predetermined length, it matches the floor thickness, which is usually about 3-5 mm. It is evenly mixed into the floor coating at a weight ratio of 0.1%, and applied on the conductive layer. A vertical magnetic field of a preset strength is applied during the construction to make the carbon fiber stand upright under the action of the magnetic field. The results are as follows: Figure 1-2 . Figure 3-4 This is a schematic diagram of a conventional carbon fiber antistatic floor.
[0079] In order to further optimize the steps, in this embodiment, the steps of the pre-synthesis method in step 1 are as follows:
[0080] Pretreatment: Select high-quality pre-oxidation fiber precursor, the pre-oxidation fiber precursor is PAN fiber, wash it with deionized water to remove surface impurities and oil stains;
[0081] Soaking reaction: The cleaned PAN fiber is immersed in a solution of ferrous chloride and ferric chloride, and the concentration of iron salt in the solution is configured at 1 mol:1 mol, so that the iron ions in the solution can completely penetrate into the fiber surface;
[0082] Precipitation formation: add an appropriate amount of sodium hydroxide solution and adjust the solution pH to 8-10, so that ferrous ions and ferric ions undergo precipitation reaction and are evenly loaded on the surface of the fiber before oxidation to form a magnetic metallization layer;
[0083] Pre-oxidation and carbonization: The fiber loaded with iron salt is heated to 250-300℃, and pre-oxidation reaction is carried out in air to form a stable iron oxide phase, and then carbonization treatment is carried out, and heating to 1000-1500℃ in a nitrogen atmosphere to generate carbon fiber and realize magnetism at the same time;
[0084] Cutting and finishing: The prepared magnetic carbon fiber is chopped into short pieces to obtain fiber segments of a certain length for subsequent use.
[0085] In this embodiment, the steps of the post-synthesis method in step 1 are as follows:
[0086] Carbon fiber preparation: select short chopped segments of waste carbon fiber, such as 3-5mm, through the waste carbon fiber recycling process, wash and dehydrate with deionized water to ensure that there are no impurities on the carbon fiber surface;
[0087] Soaking in ferrous solution: Soak the cleaned carbon fiber in a ferrous chloride solution of a certain concentration to ensure that the carbon fiber fully absorbs ferrous ions;
[0088] Precipitation reaction: slowly add sodium hydroxide solution to adjust the solution pH to 8-10 to promote the precipitation reaction of ferrous ions to generate ferrous oxide;
[0089] Heating oxidation: Immerse the soaked carbon fiber in a heating tank, raise the water temperature to 70-80°C, and maintain it for several hours to slowly oxidize the ferrous oxide on the surface of the carbon fiber into ferroferric oxide;
[0090] Magnetic activation uses high-frequency electromagnetic fields or electrostatic fields to activate the magnetic material on the surface of carbon fiber, so that it forms magnetism with controllable directionality and strength;
[0091] Surface treatment: Plasma treatment or amino treatment is performed to enhance the adhesion of carbon fiber to the coating.
[0092] In this embodiment, the details of step 2 are as follows:
[0093] Step 2.1, carbon fiber processing and mixing, first adjust the length of the magnetic carbon fiber according to the needs of the floor coating to match the floor thickness, and adjust the fiber length by mechanical cutting or chemical methods to obtain the best conductivity and coating uniformity;
[0094] The surface treatment technology is used to make the surface have good hydrophilicity or lipophilicity to enhance the bonding force with the coating. The surface treatment technology includes amino treatment, acid washing or plasma treatment;
[0095] Guided by magnetic field, the prepared carbon fiber and coating are mixed at a weight ratio of 0.1% and evenly distributed. During the coating application process, a strong vertical magnetic field is applied so that the magnetic carbon fiber is arranged into an upright shape under the action of the magnetic field, thereby optimizing the conductive network structure of the fiber;
[0096] Step 2.2, coating construction, floor coating, apply the evenly mixed magnetic carbon fiber coating to the floor surface, apply a vertical magnetic field of a certain strength during the construction process, and adjust the strength and direction of the magnetic field as needed to ensure that the carbon fibers are arranged in an upright manner during construction;
[0097] Heat treatment: After the coating is applied, it is dried and cured in a temperature-controlled environment, heated to 60-80°C to ensure that the coating is cured and the carbon fiber can maintain its upright state;
[0098] Testing and optimization: Conduct resistance testing on the finished floor coating to ensure that the density of the carbon fiber meets the anti-static requirements within a 77mm diameter circle. Further optimize the conductive properties by adjusting the amount of carbon fiber in the coating and the strength of the magnetic field.
[0099] Step 2.3, post-construction treatment, gloss adjustment, apply special gloss adjuster or transparent protective film on the coating to ensure that the floor color is more diverse and still has excellent anti-static properties, anti-wear treatment, add wear-resistant additives to the coating, wear-resistant additives include nano silicon, polyurethane materials, to improve the hardness and scratch resistance of the coating.
[0100] In this embodiment, the step 2.1 uses a dynamic frequency conversion magnetic field technology, and the frequency range is f field =50-200Hz, dynamically change the magnetic field frequency to prevent carbon fibers from gathering in the coating, calculation formula:
[0101]
[0102] D fiber : Carbon fiber distribution uniformity index;
[0103] ρ fiber : The bulk density of carbon fiber, in g / cm 3 ;
[0104] B field : applied magnetic field strength, unit: mT;
[0105] L fiber : The length of carbon fiber, in mm.
[0106] The dispersion and arrangement uniformity of carbon fibers are monitored by formulas to ensure that their distribution in the coating optimizes the conductive properties. Dynamic variable frequency magnetic field technology effectively reduces aggregation and improves the uniformity of the conductive network.
[0107] In this embodiment, the magnetic field is kept stable during the curing process in step 2.2 to ensure that the carbon fibers remain vertically aligned after the coating is cured. The calculation formula is:
[0108] S align : Fiber alignment coefficient, the value is between 0 and 1, 1 means completely vertical;
[0109] θ i : The angle between the ith fiber and the vertical direction;
[0110] n: the number of fibers tested. The arrangement coefficient is used to measure the arrangement effect of the carbon fibers. The application of the formula can monitor the effect of the magnetic field and ensure the efficient construction of the conductive network of carbon fibers inside the coating.
[0111] In this embodiment, step 2.3 also includes coating performance optimization and post-processing, and the resistance performance is optimized by adjusting the mass ratio of carbon fibers or the magnetic field strength. The calculation formula is:
[0112] R area : Surface resistance of coating, unit Ω;
[0113] ρ fiber : Resistivity of carbon fiber, unit: Ω·cm;
[0114] H floor : coating thickness, unit: cm;
[0115] A contac : Test electrode contact area, unit: cm 2 , which is used to guide the optimization of the conductive properties of the coating by adjusting parameters, including fiber density and length, to achieve the target resistance value and ensure antistatic performance.
[0116] The above method can accurately optimize and significantly improve the efficiency of the conductive network by controlling the distribution, length and arrangement of carbon fibers through formulas. It can reduce costs and reduce the amount of carbon fibers used, while improving conductivity and reducing production costs. It can improve performance and improve the conductivity and uniformity of the coating through dynamic magnetic field technology and optimization of the arrangement coefficient, and enhance the anti-static effect.
[0117] In this embodiment, the specific steps of the process flow of recycling waste carbon fiber in the post-synthesis method of step 1 are as follows:
[0118] Step 1: Pretreatment of waste carbon fiber: first, classify the waste carbon fiber to ensure that its composition is consistent with the impurity type, soak the waste carbon fiber in deionized water, clean the surface dirt, grease, and resin pollutants, use acid washing (such as diluted hydrochloric acid) or alkali washing (such as sodium hydroxide solution) to remove surface impurities according to the degree of contamination, and enhance the cleaning effect by ultrasonic cleaning, hot water cleaning or mechanical brushing. The cleaned carbon fiber is dehydrated with a drying equipment;
[0119] Step 2: Recover and remove the resin by pyrolysis or chemical dissolution;
[0120] Step 3: Soak the waste carbon fiber cleaned in step 2 in an oxidant solution to oxidize the surface of the carbon fiber to form oxygen-containing functional groups. The oxidation time and efficiency formula is:
[0121] Among them, E oxidation is the surface oxidation efficiency, A after is the surface energy of the carbon fiber surface after oxidation treatment, in mJ / m 2 , A before is the surface energy of the carbon fiber surface before oxidation treatment, in mJ / m 2 ; The carbon fiber surface modification effect can be optimized by adjusting the oxidation time and oxidant concentration.
[0122] This formula is used to evaluate the effect of carbon fiber surface oxidation treatment. The increase in surface energy means that the hydrophilicity of the carbon fiber surface is enhanced, so it can better combine with composite materials such as resin. By quantifying the oxidation efficiency, the oxidant concentration, temperature and reaction time can be adjusted according to experimental data to optimize the surface activation process of carbon fiber. Increasing the surface energy can improve the composite material binding of recycled carbon fiber and enhance its application performance in new materials.
[0123] Step 4: Magnetic enhancement treatment, magnetic material is soaked or chemically deposited onto the surface of waste carbon fiber, magnetic loading efficiency formula:
[0124] Among them, E mag is the magnetic material loading efficiency, M mag_loaded is the mass of the magnetic material loaded, in g, M total_fiber is the mass of waste carbon fiber in g. The magnetic loading effect can be optimized by adjusting the solution concentration, temperature and time. This formula is used to evaluate the loading effect of magnetic substances on the surface of waste carbon fiber. By optimizing the loading amount of magnetic material, the desired magnetic properties can be achieved while avoiding excessive use of magnetic substances. Guided by this formula, the amount of magnetic loading can be controlled to ensure that the magnetic strength meets the requirements and to avoid waste or uneven loading caused by excessive magnetic substances. Optimizing the magnetic loading efficiency helps to improve the functionality of recycled carbon fiber and adapt it to a wider range of applications.
[0125] Through the above steps, the recycling of waste carbon fiber can not only improve resource utilization efficiency, but also reduce environmental pollution. The introduction of calculation formulas helps to accurately control the key parameters in the recycling process (such as resin removal efficiency, oxidation efficiency, magnetic loading efficiency, etc.), thereby improving recycling efficiency and economic benefits. The innovativeness of this recycling process not only provides a theoretical basis for the recycling of waste carbon fiber, but also lays the foundation for large-scale application in actual production.
[0126] In this embodiment, the pyrolysis method heats the waste carbon fiber to 200-800°C, performs pyrolysis treatment in an inert gas atmosphere, removes the resin, and removes different types of resin by controlling the temperature gradient. The pyrolysis temperature formula is:
[0127] T opt : The optimal temperature for pyrolysis, T0: Initial starting temperature, indicating the minimum starting temperature for the pyrolysis reaction of the resin, M resin n: The mass of the resin, in g, affects the pyrolysis temperature requirement, C resin : The specific heat capacity of the resin, in J / g·K, indicates the heat characteristics required for the pyrolysis of the resin. The specific heat capacity of polyester resin is 1.25 J / g·K, and the specific heat capacity of epoxy resin is 1.45 J / g·K. The rate of change of resin mass with time during pyrolysis (g / min), indicating the rate of resin decomposition, k1, k2, k3: empirical coefficients, used to correct the influence of each parameter, determined according to experimental data: k1: coefficient of pyrolysis temperature with increase of resin mass, with a value of 0.4-0.6; k2: coefficient of pyrolysis temperature with change of resin specific heat capacity, with a value of 10-20, k3: coefficient of pyrolysis temperature with change of resin decomposition rate, with a value of 5-10;
[0128] In order to optimize the smoothness of temperature change, the formula for controlling the temperature gradient is:
[0129] Temperature gradient over time ℃ / min. T opt : Target pyrolysis temperature ℃, T current : Current temperature ℃, t ramp : The time required for heating up min, by adjusting t ramp , control the heating rate to make the resin decomposition more stable and avoid thermal damage to the carbon fiber surface caused by excessive heating;
[0130] Inert gas improves efficiency during pyrolysis by removing volatiles. The gas flow rate v gas The optimization formula is:
[0131] v gas : gas flow rate L / min, k4: gas flow rate influence coefficient, the value is 0.1-0.2, M resin : Initial mass of resin g. A fiber : Surface area of carbon fiber m 2 , calculated by fiber diameter and length, t gas : Gas residence time in the pyrolysis device min.
[0132] For example, the goal is to pyrolyze 10g of waste carbon fiber covered with polyester resin, with a total fiber surface area A fiber =0.05m 2 The initial temperature of the experiment is 200°C, and it is expected to complete heating and stabilization within 30 minutes.
[0133] Calculation: Optimum temperature: T opt =200+0.5·10+15·1.25+7·0.2;
[0134] T op t=200+5+18.75+1.4=225.15℃;
[0135] Temperature gradient:
[0136] Gas flow rate:
[0137] The above formula comprehensively considers the thermal properties and decomposition rate of the resin, optimizes the pyrolysis temperature, and improves the removal efficiency. The temperature gradient formula ensures a smooth heating process and avoids damage to the carbon fiber surface caused by rapid heating. By adjusting the inert gas flow rate, the volatile removal effect is improved and the energy consumption of the pyrolysis device is reduced. The formula can be flexibly adjusted according to different resin types and fiber surface conditions, and is suitable for various waste carbon fiber recycling scenarios. Through the above improvements, the pyrolysis method can recycle waste carbon fibers more efficiently and minimize resource waste and environmental pollution.
[0138] In summary, this method optimizes the preparation process of magnetic carbon fiber and the performance of floor coatings from multiple aspects. By controlling the magnetism, arrangement and distribution uniformity of carbon fiber, and combining the recycling of waste carbon fiber, it not only improves the antistatic function of the coating, but also realizes the recycling of resources and environmental protection, which has significant technical advantages and market application prospects.
[0139] This application provides the following experimental proof:
[0140] Optimization experiment 1: Carbon fiber distribution uniformity and electrical conductivity
[0141] Experimental purpose: To verify the uniformity of the distribution of magnetic carbon fiber in the coating and the conductive properties of the floor coating.
[0142] Experimental steps:
[0143] Preparation of magnetic carbon fiber coating: mixing the prepared magnetic carbon fiber with the coating at a mass ratio of 0.1%.
[0144] Applying a vertical magnetic field: A vertical magnetic field is applied during the coating application process to align the carbon fibers upright.
[0145] Curing and testing: After the coating is cured, the conductivity and fiber distribution of the coating are tested.
[0146] Dynamic variable frequency magnetic field test: Monitor the uniformity of carbon fiber distribution through dynamic variable frequency magnetic field technology.
[0147] Optimized sample 2 and optimized sample 3 were obtained.
[0148] Test parameters:
[0149] Fiber distribution uniformity: Analyze the fiber distribution through microscope images.
[0150] Resistance test: Use a surface resistance meter to test the surface resistance of the coating (unit: Ω / square).
[0151] Data Table 1: Distribution and conductivity of magnetic carbon fiber floor coatings
[0152]
[0153] Result analysis: The above method can significantly improve the distribution uniformity of magnetic carbon fibers, thereby improving the conductivity. The surface resistance of samples 2 and 3 is significantly lower than that of sample 1, indicating that the optimization of the above method has a positive effect on the conductivity of the coating.
[0154] Experiment 2: Recycling and magnetic enhancement of waste carbon fiber
[0155] Objective: To verify the magnetic enhancement effect of waste carbon fiber during recycling and compare it with conventional magnetic carbon fiber.
[0156] Experimental steps:
[0157] Waste carbon fiber processing: waste carbon fiber is recycled by pyrolysis and chemical dissolution.
[0158] Magnetic treatment: The recycled carbon fiber is magnetically enhanced by post-synthesis or pre-synthesis to obtain samples C and D.
[0159] Magnetic test: The magnetic strength of carbon fiber is tested by a magnetic tester.
[0160] Applied to floor coatings: Mix the recycled magnetic carbon fiber into the coating for floor coating.
[0161] Test parameters:
[0162] Magnetic strength: Use a magnetic tester (unit: mT) to test the magnetic properties of carbon fiber.
[0163] Resistance test: detect the surface resistance of the coating.
[0164] Data Table 2: Waste Carbon Fiber Recycling and Magnetic Enhancement Effect
[0165]
[0166] Results analysis: After recycling waste carbon fiber, the magnetic properties can be enhanced by pre-synthesis or post-synthesis, making its performance close to that of newly prepared carbon fiber, and the recycled carbon fiber shows good electrical conductivity, and the surface resistance is comparable to that of conventional carbon fiber. The magnetic enhancement effect can be further optimized by post-synthesis method (surface deposition of iron oxide).
[0167] Experiment 3: Durability and wear test of coating
[0168] Purpose: To verify the wear resistance and antistatic properties of magnetic carbon fiber floor coating.
[0169] Experimental steps:
[0170] Paint construction: Prepare the magnetic carbon fiber floor paint according to step 2 and apply it.
[0171] Wear resistance test: The wear test of the coating was carried out using a friction tester.
[0172] Resistance detection: Measure the surface resistance of the coating at different degrees of wear.
[0173] Test parameters:
[0174] Wear degree: Evaluated by wear depth (unit: μm).
[0175] Surface resistance: Use a surface resistance meter to test the surface resistance of the coating after wear.
[0176] Data Table 3: Coating Durability and Wear Test
[0177]
[0178] Results analysis: Under different degrees of wear, the surface resistance of the coating increases slightly with the aggravation of wear, but it can still maintain good antistatic performance. After wear, the conductivity of the coating decreases slightly, indicating that the technology has certain wear resistance.
[0179] Experiment 4: Effect of temperature on coating properties
[0180] Experimental purpose: To study the antistatic performance of magnetic carbon fiber floor coating in high temperature environment.
[0181] Experimental steps:
[0182] Coating construction: prepare and apply magnetic carbon fiber floor coating. Heat treatment: heat at 60℃, 80℃, and 100℃ to simulate high temperature environment.
[0183] Surface resistance test: Test the surface resistance of the coating at different temperatures.
[0184] Data Table 4: Resistance test of coating in high temperature environment
[0185]
[0186] Result analysis: With the increase of temperature, the surface resistance of the coating increases slightly, but it still remains within the anti-static requirement range, indicating that the magnetic carbon fiber floor coating has a certain high temperature stability.
[0187] Through the above experiments, it can be proved that the method of using magnetic carbon fiber to manufacture anti-static floor has significant technical advantages. Specifically, the uniform distribution of magnetic carbon fiber and the optimization of conductive properties. The recycling and magnetic enhancement of waste carbon fiber can significantly improve the performance of the material. Magnetic carbon fiber floor coating has good performance in wear resistance and high temperature stability, and is suitable for anti-static floor in various industrial environments.
[0188] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. A method for manufacturing an anti-static floor using magnetic carbon fiber, characterized in that: The steps include: Step 1, synthesizing magnetic carbon fiber. The method for synthesizing magnetic carbon fiber includes a pre-synthesis method and a post-synthesis method. The steps of the pre-synthesis method are as follows: the pre-oxidized fiber precursor is immersed in a mixed solution of ferrous chloride and ferric chloride, the concentration ratio of ferrous chloride and ferric chloride is 1 mol: 1 mol, and the pH is adjusted with a sodium hydroxide solution to precipitate ferrous ions and ferric ions, which are evenly loaded on the pre-oxidized fiber precursor. After pre-oxidation and carbonization, the carbon fiber can be magnetic when it is generated, and then the obtained fiber is chopped; The steps of the post-synthesis method are as follows: the formed carbon fiber is chopped and soaked in a ferrous ion solution, and then an alkaline substance is added to precipitate the ferrous iron, generating ferrous oxide that precipitates on the carbon fiber. The water temperature is raised to 70-80°C, and the ferrous oxide on the carbon fiber will slowly oxidize into ferroferric oxide, making the carbon fiber magnetic; Step 2: Mixing: After the prepared carbon fiber is made into a predetermined length, it is evenly mixed into the floor coating at a weight ratio of 0.1%, and construction is carried out on the conductive layer. During the construction, a vertical magnetic field of a preset strength is applied to make the carbon fiber stand upright under the action of the magnetic field.
2. The method for manufacturing an antistatic floor using magnetic carbon fiber according to claim 1, characterized in that: The steps of the pre-synthesis method in step 1 are as follows: Pretreatment: Select high-quality pre-oxidation fiber precursor, which is PAN fiber, and wash it with deionized water to remove surface impurities and oil stains; Soaking reaction: The cleaned PAN fiber is immersed in a solution of ferrous chloride and ferric chloride, and the concentration of iron salt in the solution is configured at 1 mol:1 mol, so that the iron ions in the solution can completely penetrate into the fiber surface; Precipitation formation: add an appropriate amount of sodium hydroxide solution and adjust the solution pH to 8-10, so that ferrous ions and ferric ions undergo precipitation reaction and are evenly loaded on the surface of the fiber before oxidation to form a magnetic metallization layer; Pre-oxidation and carbonization: The fiber loaded with iron salt is heated to 250-300℃, and pre-oxidation reaction is carried out in air to form a stable iron oxide phase, and then carbonization treatment is carried out, and heating to 1000-1500℃ in a nitrogen atmosphere to generate carbon fiber and realize magnetism at the same time; Cutting and finishing: The prepared magnetic carbon fiber is chopped into short pieces to obtain fiber segments of a certain length for subsequent use.
3. The method for manufacturing an antistatic floor using magnetic carbon fiber according to claim 1, characterized in that: The steps of the post-synthesis method in step 1 are as follows: Carbon fiber preparation: select short chopped segments of waste carbon fiber through the waste carbon fiber recycling process, wash and dehydrate with deionized water to ensure that there are no impurities on the carbon fiber surface; Soaking in ferrous solution: Soak the cleaned carbon fiber in a ferrous ion solution of a certain concentration to ensure that the carbon fiber fully absorbs the ferrous ions; Precipitation reaction: slowly add sodium hydroxide solution to adjust the solution pH to 8-10 to promote the precipitation reaction of ferrous ions to generate ferrous oxide; Heating oxidation: Immerse the soaked carbon fiber in a heating tank, raise the water temperature to 70-80°C, and maintain it for several hours to slowly oxidize the ferrous oxide on the surface of the carbon fiber into ferroferric oxide; Magnetic activation uses high-frequency electromagnetic fields or electrostatic fields to activate the magnetic material on the surface of carbon fiber, so that it forms magnetism with controllable directionality and strength; Surface treatment: Plasma treatment or amino treatment is performed to enhance the adhesion of carbon fiber to the coating.
4. The method for manufacturing an antistatic floor using magnetic carbon fiber according to claim 1, characterized in that: The details of step 2 are as follows: Step 2.1, carbon fiber processing and mixing, first adjust the length of the magnetic carbon fiber according to the needs of the floor coating to match the floor thickness, and adjust the fiber length by mechanical cutting or chemical methods to obtain the best conductivity and coating uniformity; The surface treatment technology is used to make the surface have good hydrophilicity or lipophilicity to enhance the bonding force with the coating. The surface treatment technology includes amino treatment, acid washing or plasma treatment; Guided by magnetic field, the prepared carbon fiber and coating are mixed at a weight ratio of 0.1% and evenly distributed. During the coating application process, a strong vertical magnetic field is applied so that the magnetic carbon fiber is arranged into an upright shape under the action of the magnetic field, thereby optimizing the conductive network structure of the fiber; Step 2.2, coating construction, floor coating, apply the evenly mixed magnetic carbon fiber coating to the floor surface, apply a vertical magnetic field of a certain strength during the construction process, and adjust the strength and direction of the magnetic field as needed to ensure that the carbon fibers are arranged in an upright manner during construction; Heat treatment: After the coating is applied, it is dried and cured in a temperature-controlled environment, heated to 60-80°C to ensure that the coating is cured and the carbon fiber can maintain its upright state; Testing and optimization: Conduct resistance testing on the finished floor coating to ensure that the density of the carbon fiber meets the anti-static requirements within a 77mm diameter circle area by adjusting the amount of carbon fiber in the coating and the strength of the magnetic field; Step 2.3, post-construction treatment, gloss adjustment, apply special gloss adjuster or transparent protective film on the coating, anti-wear treatment, add wear-resistant additives to the coating, wear-resistant additives include nano silicon, polyurethane materials to improve the hardness and scratch resistance of the coating.
5. The method for manufacturing an antistatic floor using magnetic carbon fiber according to claim 4, characterized in that: In step 2.1, the dynamic frequency conversion magnetic field technology is used, and the frequency range is f field =50-200Hz, dynamically change the magnetic field frequency to prevent carbon fibers from gathering in the coating, calculation formula: D fiber : Carbon fiber distribution uniformity index; ρ fiber : The bulk density of carbon fiber, in g / cm 3 ; B field : applied magnetic field strength, unit: mT; L fiber : The length of carbon fiber, in mm.
6. The method for manufacturing an antistatic floor using magnetic carbon fiber according to claim 5, characterized in that: In the step 2.2, the magnetic field is kept stable during the curing process to ensure that the carbon fibers remain vertically aligned after the coating is cured. The calculation formula is: S align : Fiber alignment coefficient, the value is between 0 and 1, 1 means completely vertical; θ i : The angle between the ith fiber and the vertical direction; n: number of fibers tested. The above formula is used to monitor the effect of the magnetic field and ensure the efficient construction of the conductive network of carbon fibers inside the coating.
7. The method for manufacturing an antistatic floor using magnetic carbon fiber according to claim 6, characterized in that: The step 2.3 also includes coating performance optimization and post-processing, which optimizes the resistance performance by adjusting the mass ratio of carbon fibers or the magnetic field strength. The calculation formula is: R area : Surface resistance of coating, unit Ω; ρ fiber : Resistivity of carbon fiber, unit Ω·cm; H floor : coating thickness, unit: cm; A contac : Test electrode contact area, unit: cm 2 , which is used to guide the optimization of the conductive properties of the coating by adjusting parameters, including fiber density and length, to achieve the target resistance value and ensure antistatic performance.
8. The method for manufacturing an antistatic floor using magnetic carbon fiber according to claim 3, characterized in that: The specific steps of the process flow of recycling waste carbon fiber in the post-synthesis method of step 1 are as follows: Step 1: Pretreatment of waste carbon fiber: first, classify the waste carbon fiber, soak the waste carbon fiber in deionized water, clean the surface dirt, grease, and resin pollutants, use acid or alkali washing to remove surface impurities according to the degree of pollution, and enhance the cleaning effect by ultrasonic cleaning, hot water cleaning or mechanical brushing. The cleaned carbon fiber is dehydrated with drying equipment; Step 2: Recover and remove the resin by pyrolysis or chemical dissolution; Step 3: Soak the waste carbon fiber cleaned in step 2 in an oxidant solution to oxidize the surface of the carbon fiber to form oxygen-containing functional groups. The oxidation time and efficiency formula is: Among them, E oxidation is the surface oxidation efficiency, A after is the surface energy of the carbon fiber surface after oxidation treatment, in mJ / m 2 , A before is the surface energy of the carbon fiber surface before oxidation treatment, in mJ / m 2 ; Step 4: Magnetic enhancement treatment, magnetic material is soaked or chemically deposited onto the surface of waste carbon fiber, magnetic loading efficiency formula: Among them, E mag is the magnetic material loading efficiency, M mag_loaded is the mass of the magnetic material loaded, in g, M total_fiber is the mass of waste carbon fiber, in g.
9. The method for manufacturing an antistatic floor using magnetic carbon fiber according to claim 8, characterized in that: The pyrolysis method heats the waste carbon fiber to 200-800°C, performs pyrolysis treatment in an inert gas atmosphere, removes the resin, and removes different types of resin by controlling the temperature gradient. The pyrolysis temperature formula is: T opt : The optimal temperature for pyrolysis, T0: Initial starting temperature, indicating the minimum starting temperature for the pyrolysis reaction of the resin, M resin n: The mass of the resin, in g, affects the pyrolysis temperature requirement, C resin : The specific heat capacity of the resin, in J / g·K, indicates the heat characteristics required for the pyrolysis of the resin. The specific heat capacity of polyester resin is 1.25 J / g·K, and the specific heat capacity of epoxy resin is 1.45 J / g·K. The rate of change of resin mass with time during pyrolysis (g / min), indicating the rate of resin decomposition, k1, k2, k3: empirical coefficients, used to correct the influence of each parameter, determined according to experimental data: k1: coefficient of pyrolysis temperature with increase of resin mass, with a value of 0.4-0.6; k2: coefficient of pyrolysis temperature with change of resin specific heat capacity, with a value of 10-20, k3: coefficient of pyrolysis temperature with change of resin decomposition rate, with a value of 5-10; In order to optimize the smoothness of temperature change, the formula for controlling the temperature gradient is: Temperature gradient over time ℃ / min; T opt : Target pyrolysis temperature ℃, T current : Current temperature ℃, t ramp : The time required for heating up min, by adjusting t ramp , control the heating rate to make the resin decomposition more stable and avoid thermal damage to the carbon fiber surface caused by excessive heating; Inert gas improves efficiency during pyrolysis by removing volatiles. The gas flow rate v gas The optimization formula is: v gas : gas flow rate L / min, k4: gas flow rate influence coefficient, the value is 0.1-0.2, M resin : Initial mass of resin g; A fiber : Surface area of carbon fiber m 2 , calculated by fiber diameter and length, t gas : Gas residence time in the pyrolysis device min.